Current Insight of Peptide-Based Hydrogels for Chronic Wound Healing Applications: A Concise Review - Aifa Asyhira Khairul Nizam; Syafira Masri; Nur Izzah Md Fadilah; Manira Maarof; Mh Busra Fauzi (Pharmaceuticals)
Chronic wounds present a substantial healthcare obstacle, marked by an extended healing period that can persist for weeks, months, or even years. Typically, they do not progress through the usual phases of healing, which include hemostasis, inflammation, proliferation, and remodeling, within the expected timeframe. Therefore, to address the socioeconomic burden in taking care of chronic wounds, hydrogel-based therapeutic materials have been proposed. Hydrogels are hydrophilic polymer networks with a 3D structure which allows them to become skin substitutes for chronic wounds. Knowing that peptides are abundant in the human body and possess distinct biological functionality, activity, and selectivity, their adaptability as peptide-based hydrogels to individual therapeutic requirements has made them a significant potential biomaterial for the treatment of chronic wounds. Peptide-based hydrogels possess excellent physicochemical and mechanical characteristics such as biodegradability and swelling, and suitable rheological properties as well great biocompatibility. Moreover, they interact with cells, promoting adhesion, migration, and proliferation. These characteristics and cellular interactions have driven peptide-based hydrogels to be applied in chronic wound healing.